Factors Causing The Disappearance of The Tihang Construction System in Stilt Houses Along The Kuin River, Banjarmasin City - Amelia Rizyan Nyssa; Rezha Nuraida Oktaviana (Sinektika: Jurnal Arsitektur, 2026)
Stilt houses are one type of vernacular architecture found throughout Indonesia. Each stilt house has its own construction system that has been used for hundreds of years. One of the construction systems found in the stilt houses along the Kuin River in Banjarmasin City is the Tihang Construction. This construction technique uses continuous ironwood poles from the foundation to the roof support beams and is used as the main structural pillar. There is a new phenomenon where the Tihang Construction is starting to be rarely used in today’s era. This study then aims to determine the factors causing the disappearance of the Tihang Construction system in stilt houses in the Kuin River area of ​​​​Banjarmasin City. This study used a qualitative exploratory method with field surveys and interviews. From the survey results, a total of 37 stilt houses were randomly sampled, and 11 houses were selected to become interview respondents. The results of this study indicate that the Tihang Construction is no longer used due to changes in spiritual beliefs among young people. The use of tihang was originally a belief held by nobles who owned stilt houses in ancient times, so that their homes would last longer and not be easily abandoned by their occupants. This belief turned out to be contrary to the ease and efficiency of the construction of stilt houses, so that this construction system lost its sustainability and began to be abandoned.